Changes of Mechanical Properties of Kumquat (Citrus Japonica Thunb.) and Cape Gooseberry (Physalis Peruviana L.) Fruits During Storage (Agricultural Engineering, 2016)
The selected physical properties as well as mechanical proprieties of kumquat and cape gooseberry fruit kept in the temperature of 12°C for 3 days, 8°C for 6 days and 4°C for 9 days were studied. The mass and size of fruit in three perpendicular directions were determined and density and moisture of tested material were calculated. Compressive tests of whole fruit were conducted for two directions of load application in order to determine the unit work Wp an apparent coefficient of elasticity, stress σ and strain ε. The growth of inputs of the deformation work with expansion of the storage time was confirmed with regard to kumquat fruit which is related to the decrease of their conventional density. The decrease of the stress and elasticity values coefficient of cape gooseberry fruit with higher temperatures of storing expressed with the change of the slope angle of curves of the relation of stress-deformation was proved.